Conversational Implicatures in Snow White and The Seven Dwarfs by Vera Southgate - I Kadek Rauh Suardana; I Made Suta Paramarta (Jurnal Penelitian Mahasiswa Indonesia, 2022)
Implication during a conversation is common to happen that often leads to misunderstanding between speakers and listeners. This present study aims to describe and analyze the types of conversational implicature that can be found in Snow White and The Seven Dwarfs by Vera Southgate. The present study is qualitative research applying the close reading method. The data were classified using plot segmentation in order to classify the events based on the sequence using Bordwell’s plot segmentation. The data obtained were analyzed based on Grice’s Theory of the types of conversational implicatures, and the theory of cooperative principles which are also known as maxims of speech. The research comes out with findings that there are 6 violations of conversational maxims. There are 5 violations of maxims of quantity, 2 violations of maxims of quality, 2 violations of maxims of manner, and 1 violation of the maxim of relevance. In other words, the result of the research is that there are violations in terms of conversational maxims in Snow White and The Seven Dwarfs by Vera Southgate which 50% out of the violation is maxims of quantity because, in a story, additional information during a conversation leads into another sequence of events in plot development